Public policy agenda: Analysis of the emergency aid program (EAP) from the perspective of the multiple - De Melo, Annely Ferreira; Almeida, Emmanuelle Arnaud (Seven Editora, 2023)
The COVID-19 pandemic generated a context of instability in the Brazilian economic scenario, requiring the establishment of public policies that would bring stimulus to the economic sector and that could subsidize the population during social isolation. In this sense, this chapter aims to analyze the process of formation of the governmental agenda, using the Multiple Flows Model, proposed by Kingdon (2003), to analyze the institution of the Emergency Aid Program (PAE). The methodology used to achieve the results is based on a research perspective of a qualitative, applied, exploratory and documentary nature. Data collection and analysis were concentrated on documentary collections and information in the public domain. In conclusion, data on the profile of the beneficiaries of the program in its implementation were presented.DOI:https://doi.org/10.56238/alookdevelopv1-093